2011
DOI: 10.1007/s10548-011-0210-1
|View full text |Cite
|
Sign up to set email alerts
|

Neural Signatures of Economic Parameters During Decision-Making: A Functional MRI (fMRI), Electroencephalography (EEG) and Autonomic Monitoring Study

Abstract: Adaptive behaviour requires an ability to obtain rewards by choosing between different risky options. Financial gambles can be used to study effective decision-making experimentally, and to distinguish processes involved in choice option evaluation from outcome feedback and other contextual factors. Here, we used a paradigm where participants evaluated 'mixed' gambles, each presenting a potential gain and a potential loss and an associated variable outcome probability. We recorded neural responses using autono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 118 publications
(181 reference statements)
0
14
0
Order By: Relevance
“…The vast majority of M/EEG studies in value-based decision making focused on the period after subjects receive feedback about their decisions (for example (Cohen and Ranganath, 2007;Frank et al, 2005;Pedroni et al, 2011;Yeung et al, 2005) and examine the effect of this feedback on subsequent behavior. Only few studies have assessed the temporal dynamics of the value encoding phase in humans, right after an offer presentation (Gluth et al, 2013;Hunt et al, 2012;Minati et al, 2012) but these were either based on ERP responses at single electrodes (Gluth et al, 2013;Minati et al, 2012), or were restricted within specific brain regions (Hunt et al, 2012). Our study instead examines global measures of EEG activity and provides further insight into the processes taking place while subjects see an offer and encode its value by quantifying the time of the single decision for each subject.…”
Section: Value Encoding Phasementioning
confidence: 99%
“…The vast majority of M/EEG studies in value-based decision making focused on the period after subjects receive feedback about their decisions (for example (Cohen and Ranganath, 2007;Frank et al, 2005;Pedroni et al, 2011;Yeung et al, 2005) and examine the effect of this feedback on subsequent behavior. Only few studies have assessed the temporal dynamics of the value encoding phase in humans, right after an offer presentation (Gluth et al, 2013;Hunt et al, 2012;Minati et al, 2012) but these were either based on ERP responses at single electrodes (Gluth et al, 2013;Minati et al, 2012), or were restricted within specific brain regions (Hunt et al, 2012). Our study instead examines global measures of EEG activity and provides further insight into the processes taking place while subjects see an offer and encode its value by quantifying the time of the single decision for each subject.…”
Section: Value Encoding Phasementioning
confidence: 99%
“…However, fMRI has a limited time resolution, is highly sensitive to motion artifact and can only provide an indirect measurement of neural activity. An increasing number of studies have focused on the multimodal brain mapping techniques for the research in neuroscience or physiopathology [36][37][38][39]. The other well-known functional imaging techniques include electroencephalography (EEG), magnetoencephalography (MEG), positron emission tomography (PET) and functional near infrared spectroscopy (fNIRS).…”
Section: Resultsmentioning
confidence: 99%
“…fMRI studies have shown that blood oxygen signals in the prefrontal cortex develop during economic choices where users must make gambling evaluations and expected value decisions (Minati et al 2012) and when determining decision value for different categories of goods for purchase (Grabenhorst and Rolls 2011). Using these activation patterns, Peck et al (2013a) demonstrated the use of fNIRS as input to information-filtering systems, constructing a movie recommendation engine that gradually personalized movies to the user based on predicted preference values.…”
Section: Potential Domains For Adaptive Interfacesmentioning
confidence: 99%